2011
DOI: 10.1007/s00520-010-1080-x
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and annual increase of body mass index in long-term childhood cancer survivors; relationship to treatment

Abstract: PurposeEvaluation of body mass index (BMI) at final height (FH) and annual BMI increase in adult childhood cancer survivors (CCS) after treatment with anthracyclines, platinum, and/or radiotherapy.MethodsBMI (weight/height²) was calculated retrospectively from diagnosis until FH. The prevalence of underweight (BMI < 18.5 kg/m2) and overweight (BMI ≥ 25 kg/m2)/obesity (BMI ≥ 30 kg/m2) at FH was compared with age-matched controls. The association between underweight/overweight at FH and treatment was assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“…Seventeen studies ( n = 2032 participants) reported prevalence of overweight and obesity among patients with various types of brain tumours ; The study characteristics and results are described in Table . The age at diagnosis ranged from at birth to 24.8 year old.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen studies ( n = 2032 participants) reported prevalence of overweight and obesity among patients with various types of brain tumours ; The study characteristics and results are described in Table . The age at diagnosis ranged from at birth to 24.8 year old.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence of excess overweight and obesity in SCBT compared to non‐cancer controls has been inconsistent, with some studies reporting an increase , while others finding no significant differences . The small sample size of some studies and the inclusion of different comparison groups including the general population or siblings may have contributed to these conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…This association was not seen among those treated with anthracyclines or platinum. 35 Similarly, in separate studies of survivors of childhood brain tumors and childhood ALL, cranial irradiation was associated with greater risks of overweight/obesity. 3637 Finally, Oeffinger et al found significantly increased body mass index among young adult survivors of childhood ALL treated with cranial irradiation compared to those treated with chemotherapy alone ( P =0.039).…”
Section: Why Are Childhood and Young Adult Cancer Survivors At Cvd Risk?mentioning
confidence: 98%
“…Recent clinical studies have shown that cranial radiotherapy results in metabolic sequelae, including overweight/obesity, insulin resistance, hyperlipidemia, and leptin resistance [11, 14, 17]. The incidence of obesity in childhood tumor patients who have received cranial irradiation is 40% [14].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of obesity in childhood tumor patients who have received cranial irradiation is 40% [14]. These sequelae are associated with long-term health problems, including hypertension, type 2 diabetes, depression, and cancer [17-19]. There are also sex-specific deleterious effects of cranial irradiation on metabolic function, and female tumor survivors treated with cranial irradiation have a significantly greater increase in metabolic index than male tumor survivors [14, 20-23].…”
Section: Discussionmentioning
confidence: 99%